Current Return to Sport Criteria after ACL Reconstruction Fail to Identify Increased Risk of Second ACL Injury in Young Athletes. Issue 7 (30th July 2018) - Paterno, Mark V.; Rauh, Mitchell; Thomas, Staci; Hewett, Timothy E.; Schmitt, Laura
Objectives: The incidence of 2nd anterior cruciate ligament (ACL) injury after ACL reconstruction (ACLR) and return to sport (RTS) ranges from 25%-33% in young, active populations; with the greatest risk in the first 12 months after RTS. Recent data indicate that failure to successfully meet traditional RTS criteria, inclusive of strength, functional hop testing and patient reported outcome scores, may identify athletes at increased risk of future injury after ACLR. However, these studies have focused on adult populations and it is unknown if similar RTS criteria apply to young, adolescent, pivoting/cutting athletes. The purpose of this study was to determine if meeting all current, standard RTS criteria would identify young athletes at risk for future ACL injury after primary ACLR and RTS. The tested hypothesis was the likelihood of 2 nd ACL injury in the first 2 years after RTS would be lower in patients who met all RTS criteria prior to initiation of pivoting and cutting activity compared to patients who failed to meet all RTS criteria prior to RTS. Methods: One hundred fifty-nine subjects (112 female, 47 male) with a mean age of 17.2±2.6 years old (range: 13-25 y.o.) underwent ACLR and were released to return to pivoting/cutting sport. These patients were enrolled in a prospective, observational cohort study, completed a RTS assessment and were then tracked for occurrence of 2 nd ACL after ACLR for 24 months. The RTS assessment included 6 tests: isometric quadriceps strength, 4 functional hop tests and the International Knee Documentation Committee (IKDC) patient reported outcome survey. Limb symmetry index (LSI) was calculated for strength and hop test assessments [(involved/uninvolved)*100]. The IKDC was reported on a 0-100 scale with 100 representing a perfect score. Subjects were classified into groups that successfully passed all 6 RTS tests at a level of 90 and again at 95 compared to those that failed to meet all 6 criteria. Chi Square tests were used to determine if successfully passing all 6 RTS measures at various levels of symmetry resulted in a reduced risk of 2 nd ACL injury in the first 24 months after RTS. Results: Thirty-five (22.0%) patients suffered a 2 nd ACL injury, with 26 occurring in the first 12 months after RTS. At the time of RTS, 42 patients (26%) achieved LSI values of 90 or greater on all testing as well as an IKDC value of 90 or greater. The remaining 117 subjects (74%) scored below 90 on at least 1 of the 6 assessments. At this level, there was no difference in 2 nd ACL injury prevalence between patients who passed all RTS criteria (12/42; 28.6%) and those who failed at least 1 criteria (23/117; 19.7%) (p=0.23). When the passing criteria was elevated to 95 on all RTS testing, only 15 subjects (9%) successfully passed all 6 tests. There was no significant difference in 2 nd ACL injury prevalence between patients who passed all RTS criteria (5/15; 33%) and those who failed at least 1 test (30/144; 20.8%) (p=0.32). Sub-group analysis which evaluated the group by graft type, also indicated no significant differences between groups (p>0.05). Conclusion: Current criteria to evaluate readiness to return young athletes to pivoting and cutting sports, using quadriceps strength symmetry, functional hop performance symmetry and patient reported outcomes, may not identify young, active patients at high risk for 2 nd ACL injury. Future work must identify more appropriate criteria to assess readiness to RTS in the young, athletic population and incorporate these findings into practice.